Simultaneous saccharification and fermentation of native rye, wheat and triticale starch. (18th May 2019) - Strąk‐Graczyk, Ewelina; Balcerek, Maria; Przybylsk, Katarzyna; Żyżelewicz, Dorota
Abstract: BACKGROUND: The increasing global demand for starchy raw material requires new methods for obtaining ethanol from a range of plants using environmentally friendly methods. Granular starch‐hydrolyzing enzymes (GSHE) can effectively support the development of the distillery industry. RESULTS: The aim of this study was to evaluate the effectiveness of simultaneous saccharification and fermentation of native rye, wheat or triticale starch. Mashes were prepared using methods that limit water and energy consumption (pre‐hydrolysis at 35 °C for 30 min). The results show that the degree of starch saccharification depended on the raw material. However, the highest yields of ethanol were obtained with 100 kg of triticale mashes (38.9 ± 1.4 L absolute alcohol) as compared to rye and wheat mashes. The concentration of dry matter (between 250 and 280 g L −1 ) in the mashes was not associated with a decrease in ethanol yield and improved efficiency in the case of wheat and triticale. CONCLUSION: Simultaneous saccharification and fermentation offers a low‐cost and environmentally friendly alternative to existing procedures for industrial ethanol production, which may be of particular interest to raw‐spirit producers, as well as to the food and fermentation industry at large. © 2019 Society of Chemical Industry